Spain Campaign Committee : our appeal (circular) (1937)
1937 THE LABOUR PARTY SPAIN CAMPAIGN COMMITTEE OUR APPEAL We appeal to all the members of the Party for their active and enthusiastic co-operation in this Campaign. Winter is upon us. "So far, nothing is lost and nothing is won in Spain." Democratic Spain is getting ready to spend its second winter in the trenches. The People's Army now exists. Again and again its courage has been proved on many battle-fronts. But Democratic Spain is not merely confronted with enemies within. It has now been recorded by the Assembly of the League of Nations that there are foreign army corps in Spain. Our Spanish friends have to defend their freedom on the field of battle against the men and resources of Hitler and Mussolini. The war in Spain is an international war. The duty which is imposed upon us is an international Socialist duty. We owe it to those who fight and to those who suffer in Spain not to be guilty of moral desertion, but to testify to our faith in them and in their Cause on every possible opportunity. We are not neutrals in this conflict. We have never been neutrals; we never will be neutrals; we cannot be neutrals. We fervently desire the victory of the Spanish Republicans, who are giving their lives to defend Democracy in Spain. If Spain is lost to Democracy, Hitler and Mussolini will be able to inscribe on their blood-stained banners the name of yet another people whose only crime is their love of freedom. We have a political obligation to renew and intensify our agitation against the restrictions which are imposed on the Spanish Government in the purchase of the weapons indispensable for victory. We demand unconditional freedom of commerce for the Spanish Government in the purchase of arms. We demand the immediate withdrawal of the foreign troops in Spain, in order to put an end to a shameful act of aggression. We oppose the concession to Franco, under the name of belligerent rights, of the right to search, sink or detain ships on the high seas carrying food supplies and war material to Democratic Spain. We oppose any concessions in international law and status to Franco. He is a rebel. His troops are invaders. His ships are pirates. A second winter of war in Spain brings home to us other duties. And Governments cannot, or dare not, hinder us in the fulfilment of these imperative duties. Democratic Spain has to endure a stupendous internal strain on its economic resources. Civil war not only divides a country: its economic and human resources are disorganised. The needs of the army have first claim. But when the armies of Franco advance, refugees flee elsewhere. It is officially estimated that there are now 800,000 refugees in Catalonia alone. From a recent report published in the "Lancet," October 16, 1937, we get a glimpse of conditions in Catalonia. Doctors Ellis and Russell tell us that at the end of September there were half a million refugees in Catalonia, 37,000 in Barcelona alone, who had to be entirely supported by Assistencia Social. Others were living somehow independently. Refugees were still arriving. With the new influx from the North of Spain, the problem of assistance was becoming desperate. Food is scarce. " The shortage of milk is universal. One colony of 225 refugees (in which there were 135 children under fourteen) had only four tins of condensed milk a day, the four cows allotted to the colony having had to be killed on account of tuberculosis." " Whilst milk remains the most crying need, there is also a great shortage of bread . . . ." " Nutritional anaemia, particularly among the younger children, is already becoming apparent . . . ." " There is also a lack of soap." But "the most urgent necessity of the moment is for milk." " Life among the Ruins of Madrid " has been described in " The Times " (October 30, 1937) in an article " From a Correspondent Lately in Spain." It is stated in this article that on September 1 last the number of persons holding ration cards was 806,077. Only 11lb. of solid food, nearly two-thirds of it being bread, is obtainable with ration cards for one person for a month. Milk, eggs and fresh fish are reserved for invalids with medical certificates, who, however, are never sure of the ration. Children under four years of age receive a daily ration of milk. We shall appeal, during the present campaign, for Milk for Democratic Spain. We shall demand Freedom, Food and Justice for Democratic Spain and the ending of Fascist intervention. C.P.S. (T.U., 44 hours). Tudor St., London. E.C. 4- 87573 292/946/16b/18(iii)